2016
DOI: 10.1177/0954406216638881
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on the unsteady effect of axial spacing on the performance in a contra-rotating axial compressor

Abstract: Unsteady numerical simulations are conducted to investigate the unsteady effects of axial spacing on the performance of a contra-rotating axial compressor. The results show that the stage efficiency is dominant by unsteady effects between two rotors at lower axial gap ranges. As the axial spacing is increased, the variation of aerodynamic force is different for the two rotors. As a whole, the oscillation on the pressure surface is much stronger than that on the suction side in rotor1. For rotor2, however, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Their findings indicated that by decreasing the axial spacing between the blade rows, an increase in efficiency and static pressure coefficient was achieved. Liu et al [7] results consistent with those of Smith [5] and Zak [6], investigated the effect of the axial spacing of the blade rows on the contra-rotating compressor.…”
Section: Introductionsupporting
confidence: 63%
“…Their findings indicated that by decreasing the axial spacing between the blade rows, an increase in efficiency and static pressure coefficient was achieved. Liu et al [7] results consistent with those of Smith [5] and Zak [6], investigated the effect of the axial spacing of the blade rows on the contra-rotating compressor.…”
Section: Introductionsupporting
confidence: 63%
“…Nouri et al [12] conducted an experimental investigation on the inverse design method of contra-rotating axial fans and the effects of varying the axial distance and rotational speed ratios on the overall performance were analyzed. Mao et al [13] investigated the effects of axial distance on the performance of a contra-rotating axial fan by unsteady numerical simulation. The results suggested that the unsteady effects dominated the flow behavior at smaller axial spacing ranges, while the variation of aerodynamic force for two rotors was different as the axial spacing increased.…”
Section: Introductionmentioning
confidence: 99%
“…It was further shown that at design speed the axial spacing did not significantly affect the stage performance, but at offdesign speeds an optimum axial distance could be determined. A numerical study of unsteady effects of axial spacing in a contra-rotating compressor was conducted by Mao and Liu, 7 which emphasized the importance of a proper choice of the design axial distance between the two rotors. A transonic two-stage contra-rotating compressor was designed, built and tested by Wilcox and Wright 8 and Wilcox and Stevans.…”
Section: Introductionmentioning
confidence: 99%